Answer to the letter to the editor titled 'Phenoxyethanol, reproduction, and development: additional studies are needed'. (31st July 2020) - Dréno, B.; Zuberbier, T.; Gelmetti, C.; Gontijo, G.; Marinovich, M.
Abstract : Linked article: R. Garlantézec, et al. J Eur Acad Dermatol Venereol 2020;34:e407–e408. https://doi.org/10.1111/jdv.16344 .